Problematika Pembentukan RUU Cipta Kerja Dengan Konsep Omnibus Law - Kurniawan, Fajar (Fakultas Hukum Universitas PGRI Kanjuruhan Malang, 2020)
Abstract : This research was conducted to find out the problem of formation a bill that regulate employment with the concept of the Omnibus Law which was rejected by workers in the labor cluster that regulates about severance pay given to dismissed workers. This study uses a statue approach, conceptual approach, and case approach to make it easier to understanding the problem in that field. The results of the study was found that the amendment to the severance provisions in article 156 of Law with number 13 of years 2003 concerning the employment bill in Article 89, absolutely did not provide a solution of the occured problems so far. With these changes narrowed the labor rights and widen employers to exploit labor for his self profit . Therefore the Government and the Parlement should give a better solution to give welfare and certainty to workers and employers in the Employment Cluster Work Bill in Article 89 number 45 so that it can provide a good impact on the country. Keyword: Omnibus Law, Regulation, Severance